Building Coalitions: Working With Diverse Cultures - Bill Smith; Ann W. Miller; Thomas Archer; Carla E. Hague; Elizabeth B. Bolton; Lisa A. Guion (EDIS)
This document is FY508, Part 16 of the 16 part series adapted for use in Florida by Elizabeth B. Bolton and Lisa Guion. Reprinted with permission March, 1997. Revised April, 2002.